"What are you studying, my boy?!" : experience of studying social pedagogy in perspective of male students - Ćosić, Andrea (Array, 2018)
Considering the ratio of male and female professionals in social pedagogy, a smaller number of male professionals is no‑ ticeable. In an effort to expand the understanding of this social phenomenon, research has been conducted that is inspired by the deliberations on the characteristics of men who choose to become social pedagogues and how they feel about studying and working in a profession where women are the majority. An additional significance of this topic is that it is mostly unexplored in the context of social pedagogy. The aim of the paper was to explore the experience of studying social pedagogy from the perspective of male students. A qualitative approach was used in the research in which the data was collected by using the focus group method. Focus groups included thirteen male students of undergraduate and graduate studies of Social Pedagogy enrolled during the academic year 2015/2016. The results indicated that male students who enrolled in the study of Social Pedagogy are motivated by their interest in criminology and penology subjects and the uniqueness of social pedagogical work. Participants noticed positive discrimination towards male social pedagogues in employment and work. The results also pointed to student satisfaction with the study programme and their experience of increasing personal awareness during the study. Since Social Pedagogy is focused on taking care of individuals/groups, it is important to consider the impact of professionals’ gender roles in their everyday work. Accordingly, the paper focuses on the professional and personal perspective of male social pedagogues and thus contributes to the development of new topics related to gender roles and professional identity of social pedagogues.